Studies on the effect of tryptophan substitutions in channel-forming peptide: CK4M2GLYR - Layman, Jammie (Kansas State University, 2014)
NC-1007 (CK₄-M2GlyR) (PARVGLGITTVLTMTTQSSGSRAKKKK) is a synthetic peptide modeled after the second transmembrane segment of the spinal cord glycine receptor’s α-subunit, and has demonstrates the capacity to oligomerize to form transmembrane channels with Cl[superscript]- permselectivity. While studies into the effects of truncation on both CK[subcript]4 (C-terminal tetra-lysl adducted) and NK[subscript]4 (N-terminal tetra-lysl adducted) led to more control over solution aggregation in the NK[subscript]4 variant, the work presented explore whether C-terminal sequential substitutions with a tryptophan residue could similarly stabilize the aqueous structure in monomeric form or further define the pore registry in such a way as to promote an increase ion permeability. Tryptophan was substituted for amino acids in the 18[superscript]th, 19[superscript]th, 20[superscript]th, and 21[superscript]st positions of the peptide sequence (SSGS, respectively), and changes in aggregation profiles, secondary structure, and channel ion permeability were observed. Synthesized peptides show circular dichroism spectral profiles indicating that the studied tryptophan substitutions did not result in a reduction of the characteristic helicity of the peptide; however, the tryptophan substitution also did little to decrease solution aggregation as demonstrated by comparative studies by reverse-phase high- performance liquid chromatography. All peptides demonstrated channel activity, directly measured by recordings of transepithelial short-circuit current. with profiles that suggest trends in electrostatic interactions and membrane registry relative to substitution position. One peptide in particular, NC-1007 S21W displayed atypical activity, which could not be effectively described by the standard Hill-based model but may be indicative of an ill-defined registry due to the substituted peptide’s proximity to another strongly pore-defining residue. Further studies in the effects of sequence modification to channel-forming peptides will elucidate how sequences may be altered to optimize synthetic peptide solubility, resistance to in-solution aggregation, and ability to form selective and permeable ion channels. The understanding gained from this study will improve our ability to develop peptides that could serve as a therapeutic treatments for a number of endogenous channelopathies.
Keywords: Ion Channel Peptide Cystic Fibrosis; Biochemistry (0487); Biophysics (0786)